Beyond Curry: Turmeric’s Formulation Journey in Pharmaceutical Sciences - Vyas, Ujwal (Asian Journal of Pharmaceutics (AJP), 2024)
Turmeric, one of the most effective herbal remedies, belongs to the Zingiberaceae family. Most of the studies have shown that curcumin is the main cause of the majority of the positive effects of turmeric. It is good for a number of things and has antioxidant qualities helpful for diseases, such as leukemia, diabetes, allergy symptoms, arthritic conditions Alzheimer’s illness, and other persistent, hard-to-treat conditions illnesses are all examples. This review’s objective was to offer a succinct summary of the most recent information on curcumin’s effects. In international journals, such as PubMed/Medline, Science Citation Index, and Google Scholar, they searched for recent literature concerning turmeric. Turmeric’s usefulness in treating a variety of illnesses, especially those brought on by oxidative stress, such as cancer, diabetes, and inflammatory conditions, has been supported by recent studies. It also contains anti-HIV, anticoagulant, and hepatoprotective properties. The spice curcumin shows considerable potential as a medicine. It is remarkably non-toxic as well. The creation of modern pharmaceuticals based on curcumin should be addressed for the treatment of many diseases since the global landscape is evolving toward the use of non-toxic plant products with traditional medicinal properties. To do so, further study on turmeric is needed to investigate uncharted areas and their real-world therapeutic applications that may be used for the benefit of humanity, phroprotective qualities that aid in the battle against AIDS. Curcuma longa is the scientific name for turmeric. It has protective, renal, and antimicrobial benefits.